Lessons from eight projects and implications for integrated agriculture-health projects - Johnson, Nancy L.; Kovarik, Chiara; Meinzen-Dick, Ruth S.; Njuki, Jemimah; Quisumbing, Agnes R. (International Food Policy Research Institute, 2015)
What is the impact of agricultural development projects on women’s and men’s assets?